2022
DOI: 10.3390/ijerph19010556
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Enhanced 4Active Intervention Impacting Psychological Well-Being and Physical Activity among Older Adults: A Pilot Study

Abstract: Background: To increase psychological well-being and physical activity (PA) behaviors, our pilot study used the social ecological model as the framework to design the 4Active intervention, focusing on multicomponent exercise group lessons at the interpersonal level and self exercise enhanced by activity trackers at the individual level. The purpose of this pilot study was to examine the effectiveness of the two-level 4Active intervention in improving psychological well-being and PA participation in older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…It is possible that the greater playfulness of activities performed in CRA influenced this outcome. Previous studies have indicated favorable psychological responses in individuals performing PA in groups versus individually, 56 in natural environments, 40 or in programs that value native sociocultural contexts. 57 The CRA approach highlights sociocultural traditions meaningful for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the greater playfulness of activities performed in CRA influenced this outcome. Previous studies have indicated favorable psychological responses in individuals performing PA in groups versus individually, 56 in natural environments, 40 or in programs that value native sociocultural contexts. 57 The CRA approach highlights sociocultural traditions meaningful for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have shown that modern technology, including wearable devices and mobile apps, can be practical tools in maintaining physical activity levels after completing CR [33,34]. In particular, older adults have demonstrated a strong potential for adopting new technologies to support their physical activity and maintain healthy lifestyles [35,36]. For example, in a previous study, we found that a home-based CR program that included wearable activity trackers and web-based support was well received by older adults who reported improved physical activity levels and overall satisfaction with the program [37].…”
Section: Principal Findingsmentioning
confidence: 99%